Insertion of terminal alkyne into Pt–N bond of the square planar [PtI2(Me2phen)] complex12. Issue 45 (3rd November 2017) - Benedetti, Michele; De Castro, Federica; Lamacchia, Vincenza; Pacifico, Concetta; Natile, Giovanni; Fanizzi, Francesco P.
Abstract : The reactivity of [PtX2 (Me2 phen)] complexes (X = Cl, Br, I; Me2 phen = 2, 9-dimethyl-1, 10-phenanthroline) with terminal alkynes is reported. Bromo and iodo derivatives lead to the formation of Pt(ii ) alkenyl derivatives of the type [PtX2 κ 2 - N, C -( Z )-N̲1–N10–C̲{C(H)(R)] (N1–N10 = Me2 phen) containing a Pt–N–C–C–N–C six membered metallacycle. Abstract : The reactivity of [PtX2 (Me2 phen)] complexes (X = Cl, Br, I; Me2 phen = 2, 9-dimethyl-1, 10-phenanthroline) with terminal alkynes has been investigated. Although the dichlorido species [PtCl2 (Me2 phen)] exhibits negligible reactivity, the bromido and iodido derivatives lead in short time to the formation of five-coordinate Pt(ii ) complexes of the type [PtX2 (Me2 phen)(η 2 -CH}CR)] (X = Br, I; R = Ph, n -Bu), in equilibrium with the starting reagents. Similar to analogous complexes with simple acetylene, the five coordinate species can also undergo dissociation of an halido ligand and formation of the transient square-planar cationic species [PtX(Me2 phen)(η 2 -CH}CR)] + . This latter can further evolve to give an unusual, sparingly soluble square planar product where the former terminal alkyne is converted into a :C{C(H)(R) moiety with the α-carbon bridging the Pt(ii ) core with one of the two N-donors of coordinated Me2 phen. The final product [PtX2 κ 2 - N, C -( Z )-N̲1–N10–C̲{C(H)(R)] (N1–N10 = 2, 9-dimethyl-1, 10-phenanthroline; X = Br, I) contains a Pt–N–C–C–N–C six-membered chelate ring in a square planar Pt(ii ) coordination environment.